2021
DOI: 10.1007/s10856-021-06581-z
|View full text |Cite
|
Sign up to set email alerts
|

Biocompatibility studies of polyurethane electrospun membranes based on arginine as chain extender

Abstract: Electrospun polymers are an example of multi-functional biomaterials that improve the material-cellular interaction and aimed at enhancing wound healing. The main objective of this work is to fabricate electrospun polyurethane membranes using arginine as chain extender (PUUR) in order to test the fibroblasts affinity and adhesion on the material and the polymer toxicity. Polyurethane membranes were prepared in two steps: (i) the polyurethane synthesis, and ii) the electrospinning process. The membranes were ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 51 publications
(96 reference statements)
0
6
0
1
Order By: Relevance
“…Likewise, it was not tested whether any solvent residues might be retained in the nanofibrous scaffolds, which may cause toxic effects upon release into the culture medium. [119][120][121] To address this potential cytotoxicity of PCL and PCL:cellulose derivative electrospun scaffolds, LIVE/DEAD assays based on viable and nonviable cell-selective permeability to fluorescent dyes could be performed at several timepoints during in vitro culture. [119,122] Moreover, it would be beneficial to incubate all cells with leachates from all scaffold formulations, in order to assess whether any toxic products are released from the nanofibers into the culture media.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Likewise, it was not tested whether any solvent residues might be retained in the nanofibrous scaffolds, which may cause toxic effects upon release into the culture medium. [119][120][121] To address this potential cytotoxicity of PCL and PCL:cellulose derivative electrospun scaffolds, LIVE/DEAD assays based on viable and nonviable cell-selective permeability to fluorescent dyes could be performed at several timepoints during in vitro culture. [119,122] Moreover, it would be beneficial to incubate all cells with leachates from all scaffold formulations, in order to assess whether any toxic products are released from the nanofibers into the culture media.…”
Section: Discussionmentioning
confidence: 99%
“…[119][120][121] To address this potential cytotoxicity of PCL and PCL:cellulose derivative electrospun scaffolds, LIVE/DEAD assays based on viable and nonviable cell-selective permeability to fluorescent dyes could be performed at several timepoints during in vitro culture. [119,122] Moreover, it would be beneficial to incubate all cells with leachates from all scaffold formulations, in order to assess whether any toxic products are released from the nanofibers into the culture media. [119] Of note, only basic biocompatibility analyses were conducted, and it would be interesting to further evaluate the performance of these formulations in terms of tissue functionality (i.e., gene and protein expression, tight junction formation).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alves et al found that the plasma treatment process on polyurethane increased the hydrophilicity [51]. In addition, several research groups have investigated improving cell attachment on such polymeric surfaces [57][58][59][60][61]. Plasma activation and TiO 2 deposition were utilised as a surface treatment to improve cell adhesion and aid tissue ingrowth into the implant [62].…”
Section: Surface Modification To Gord Implant To Improve Biological R...mentioning
confidence: 99%
“…Existem mais de 2.000 tipos de coberturas disponíveis no mercado internacional para o tratamento de feridas e queimaduras, sejam eles sintéticos ou biológicos. Os produtos com base polímera são progressivos e os curativos são úteis nesses tratamentos de feridas em razão de sua porosidade, da epitelização, do desempenho mecânico, além da biodegradabilidade e biocompatibilidade, desde ocorram técnicas de consolidação de permanência que impeçam a reabsorção e as falhas do material (Takejima et al, 2021;Venegas-Cervera et al, 2021;De Barros et al, 2022).…”
Section: Introductionunclassified